The effectiveness of natural adsorbents for multi dye system - Teh Ubaidah, Noh (2010)
Natural materials have been investigated as potential industrial adsorption media. The uses of natural adsorbents in wastewater treatment have received increasing attention and currently offer a very attractive method for pollution remediation. The main purpose of this research was to study the effectiveness of natural adsorbents for the multi dye system removal (synthesis wastewater) by adsorption technique in batch process. The natural adsorbents that had been used were wood ash, papaya seed, coconut husk and clay. The operation parameters investigated included the effect of the pH towards dyes removal performance and optimum dosage of natural adsorbents for multi dye system. Different range of pH that had been used was pH 3 (acidic), pH 7 (neutral) and pH 11 (basic) in different dosage of adsorbents. In this research, the percentage of dye removal for MO showed higher compared than percentage of dye removal for MB. The residual of dye concentration was determined spectrophotometrically by monitoring absorbance changed at maximum wavelength adsorption using UV-Vis spectrophotometer. After analyzed the data, wood ash was found as the effective natural adsorbents in multi dyes system compared with coconut husk, papaya seeds and clay. In pH 3 (acidic), it produced higher percentage of dyes removal. The pH of the solution affects the surface charge of adsorbents as well as the degree of ionization of dyes. The equilibrium data were further analyzed using the linearized form of Freundlich and Langmuir isotherm. The coefficient of correlation R2 was high for Freundlich and Langmuir isotherm based on pH of adsorbents. The Freundlich isotherm takes place on heterogeneous surface with a non-uniform distribution of heat adsorption over the surface while the Langmuir model based on monolayer, uniform and finite adsorption site assumptions. Lastly, this research indicated that natural adsorbents could be employed as an alternative for wastewater treatments besides it is not only to minimize the cost, but also to improve the profitability.